Asymptotic bias for GMM and GEL estimators with estimated nuisance parameters - Newey, W.K.; Ramalho, J.J.S.; Smith, R. J. (Identification and Inference for Econometric Models: Essays in Honor of Thomas Rothenberg, 2005)
This chapter studies and compares the asymptotic bias of GMM and generalized empirical likelihood (GEL) estimators in the presence of estimated nuisance parameters. We consider cases in which the nuisance parameter is estimated from independent and identical samples. A simulation experiment is conducted for covariance structure models. Empirical likelihood offers much reduced mean and median bias, root mean squared error and mean absolute error, as compared with two-step GMM and other GEL methods. Both analytical and bootstrap bias-adjusted two-step GMM estimators are compared. Analytical bias-adjustment appears to be a serious competitor to bootstrap methods in terms of finite sample bias, root mean squared error, and mean absolute error. Finite sample variance seems to be little affected.